CASE REPORT ABOUT THE PROSTHETICS WITH INTRAOSSEOUS IMPLANTS OF THE MAXILLA - Desislava Konstantinova; Anna Nenova-Nogalcheva (Peytchinski Publishing, 2021)
During the rehabilitation of patients with the atrophic maxilla, the dental medicine doctor may faced before the challenge of achieving the exact placing of the intraosseous implants. We would like to present you the case of a 33-year woman with a prosthetic of implants after a Rehermanns plastic. The clinical and radiographic examinations show an absorbed maxilla with the horizontal and vertical bone deficit. The patient used a placeholder till the complete bone restoration after the surgical intervention. She did not want a final rehabilitation of the defect using a bridge-like structure due to the necessary intervention of the teeth neigboring the defect. The decision about the placing of intraosseous implants was made after the CBCT examination. The control examinations made after 6 months, 1 year, 3 years, and 5 years show satisfying results in regard to the function and aesthetics, and also the lack of subjective sensation for the patient.